2020
DOI: 10.1097/md.0000000000018852
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physicians’ knowledge on outpatient antibiotic use

Abstract: We designed this study to explore how factors, especially knowledge, influence the use and prescriptions of antibiotics among physicians in China's county hospitals. A questionnaire was designed to evaluate the knowledge levels of physicians. The rates of antibiotic prescriptions were collected through on-the-spot investigations. The percentage of encounters with antibiotics prescribed and the percentage of encounters with antibiotics combination prescribed were used to measure antibiotics use. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In practice, clinical pharmacists can fill the gap by working as an integral member in the MDT and offering optimal antimicrobial therapies according to infection sites, pathogens, pharmacokinetics/pharmacodynamics (PK/PD) parameters of antibiotics, and patients' renal or liver function (Zhou et al, 2016;Wang et al, 2019). In addition to consulting pharmacists on antibiotic selection and dosing, it may also be important to set up more targeted courses to equip ICU physicians with essential knowledge on antibiotic use (Guan et al, 2019;Wushouer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, clinical pharmacists can fill the gap by working as an integral member in the MDT and offering optimal antimicrobial therapies according to infection sites, pathogens, pharmacokinetics/pharmacodynamics (PK/PD) parameters of antibiotics, and patients' renal or liver function (Zhou et al, 2016;Wang et al, 2019). In addition to consulting pharmacists on antibiotic selection and dosing, it may also be important to set up more targeted courses to equip ICU physicians with essential knowledge on antibiotic use (Guan et al, 2019;Wushouer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, clinical pharmacists could fill the gap by working as an integral member in the MDT and offering optimal antimicrobial therapies according to infection sites, pathogens, pharmacokinetics/ pharmacodynamics (PK/PD) parameters of antibiotics, and patients' renal or liver function [37,38]. In addition to consulting pharmacists on antibiotic selection and dosing, it may also be important to set up more targeted courses to equip ICU physicians with essential knowledge on antibiotic use [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Wushouer and colleagues in China reported that the higher the knowledge of the practitioners, the lower the rate of antibiotic prescribing [26]. This was also reported in a German study that assessed the effect of knowledge about antibiotic resistance on the prescribing pattern among practitioners; awareness about antimicrobial resistance highly influenced the practitioners' pattern in prescribing antibiotics to their patients, and this was confirmed in additional studies in Iran and Croatia [27][28][29].…”
Section: Discussionmentioning
confidence: 66%